"Our turn to eat:" Shifting gender norms and food security in the Wakiso district of Uganda. Issue 3 (4th May 2019) - Durairaj, Amialya E.; Gewa, Constance A.; Komwa, Maction K.; Pawloski, Lisa
ABSTRACT: Evidence suggests that household inequalities contribute to food insecurity and nutrient deficiencies in rural Ugandan women. In this mixed-methods study, 64 participants from two villages in the Wakiso District were interviewed and asked questions from FANTA's Household Food Insecurity Access Scales (HFIAS) tool. Participants detailed foods consumed within the last 24 hr; these data were used to create Household Dietary Diversity (HDDS) scores. Discussion group qualitative data were evaluated through thematic analysis. There was no statistically significant evidence to suggest that the gender of the head of the household influenced these scores. The mean HFIAS score was 9.3 out of 27 and the mean HDDS was 6.4 out of 14. The qualitative data paints a picture of economically independent women who are overburdened by household responsibilities. Additionally, participants reported limited access to marketplaces to sell crops directly and therefore sold to agricultural middlemen. Technical investments in low-cost storage technologies are recommended to ensure more negotiation power with middlemen while also improving household food security.